A data quality framework, method and tools for managing data quality in a health care setting: an action case study. (15th May 2018) - Bai, Lu; Meredith, Rob; Burstein, Frada
Abstract: The effectiveness, efficiency and reliability of health services depends on the quality of data in health information systems used by health care providers, managers and decision-makers. The aim of this research-in-progress paper is to propose a data quality framework, method and set of tools to help an information management team at a health care institution to monitor data quality as part of their business intelligence process. The proposed tool has the capacity to capture and visualise different stakeholder perceptions of data quality depending on the user role and the task they are responsible for. This study uses an action case method to develop a prototype of the tool and provide an illustration of its implementation and usage by multiple stakeholders.